A survey of public eye-care behavior and myopia education - Liu, Qianwen; Chen, Moxin; Yan, Tongtong; Jiang, Na; Shu, Qin; Liang, Xiaoyi; Tao, Zhuoran; Yang, Xuefeng; Nie, Wanqin; Guo, Yonglin; Li, Xiaojing; Zhu, Deyi Jasmine; et al. (Frontiers in Public Health, 2025)
PurposeTo investigate the prevalence of myopia, analyze public eye care behaviors, eye protective practices, and concerns regarding myopia among different age demographics. It also aimed to provide suggestions for improving the dissemination of science popularization about myopia, taking into account different age groups.MethodsBetween May 2022 and July 2022, we gathered data from participants through online questionnaire surveys and subsequently analyzed the collected responses.ResultsThe research encompassed a total of 393 individuals, out of which 331 were identified as having myopia. The chi-square test revealed significant correlations between myopia and age (χ2 = 18.7, P = 0.002), comprehensiveness of eye examinations (χ2 = 5.0, P = 0.025), and adherence to the “20-20-20” rule (χ2 = 6.1, P = 0.014). Furthermore, there were notable variations in the frequency and comprehensiveness of eye examinations (χ2 = 14.0, P = 0.016), adherence to the “20-20-20” rule (χ2 = 25.267, P < 0.001), and levels of concern regarding myopia (χ2 = 63.8, P < 0.001) observed across different age groups. Participants aged 17 and below demonstrated a primary interest in acquiring fundamental knowledge about myopia. The 18–25 age group expressed a particular interest in strategies for managing myopia. Conversely, people between the ages of 36–45 are more concerned about whether the many rumors about myopia that have not been medically proven, such as “myopia can be cured,” are true.ConclusionAs the policies and awareness regarding myopia improve, younger people are adopting better eye-care behaviors in comparison to older populations. Enhancing visual health and reducing the occurrence of myopia requires the improvement of age-appropriate science popularization.